Development of the method for geometric modeling of S-shaped camber line of the profile of an axial compressor blade - Borisenko, Valeriy; Ustenko, Serhiy; Ustenko, Iryna (Eastern-European Journal of Enterprise Technologies, 2019)
The method for geometric modeling of the S-shaped camber line of the profile of an axial compressor blade, which is a compound curve formed from three sections, was developed. Each of these sections is modeled in the natural parameterization using certain laws of curvature distribution along the arc of the modeled curve. The curvature of the input section obeys the linear law and that of the other two obeys the quadratic law of distribution from the length of the proper arc. Sections are connected with ensuring the second order of smoothness which implies the equality of the values of functions, derivatives, and the curvature at the conjugation point. In contrast to existing methods, it is proposed to plot the camber line of the compressor blade profile directly in the cascade of profiles, for which the axial length, stagger angle and its chord are known. In this case, the geometric angles of flow inlet and outlet are used as source data. Giving the S-shape to the camber line of the blade profile will facilitate multi-gradient motion of working medium at the outlet of the cascade of the profile, and therefore reduce energy losses in a compressor. Based on the proposed method, we developed a software code, which, in addition to digital information on the modeled camber line of the compressor blade profile, also displays the obtained results in a graphical form on the screen of a computer monitor. The performed calculation and experimental studies proved the efficiency of the proposed method for modeling camber lines of the profiles of axial compressor blades. This method can be useful to the organizations involved in designing axial compressors for gas turbine engines